The Influence of Environmental Performance and Corporate Reputation on Financial Performance with Corporate Social Responsibility as an Intervening Variable - Phitaloka, Nimas Galuh; Dearani, Ninka; Abdianto, Ahmad; Mujanah, Siti; Fianto, Achmad Yanu Alif (PT Inovasi Pratama Internasional, 2025)
This study aims to examine the impact of environmental performance and corporate reputation on financial performance, with Corporate Social Responsibility (CSR) serving as an intervening variable. CSR, which reflects a company's social responsibility, is suspected of acting as a bridge that strengthens the relationship between environmental performance, corporate reputation, and financial performance. In the highly competitive business era, environmental performance and corporate reputation, particularly in achieving optimal financial performance, are important factors that influence a company's success.The study uses secondary data from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) and employs path analysis to test the causal relationships between variables. The results show that environmental performance and corporate reputation have a positive influence on financial performance, both directly and through CSR as an intervening variable. These findings provide important implications for company management to pay more attention to environmental and social aspects in their business strategies to sustainably improve financial performance